On the Vote Purchasing Behavior of Incumbent Governments - Matz Dahlberg; Eva Johansson (Uppsala University, Department of Economics, 1999)
A couple of months before the Swedish election in 1998, the incumbent government distributed 2.3 billion SEK to 42 out of 115 applying municipalities. This was the first wave of a four-year long grant program intended to support local investment programs aimed at an ecological sustainable development. This temporary grant program differs from traditional intergovernmental grants in several aspects, most importantly in the sovereign decision making power given to the incumbent central government. In this paper we investigate whether there were any tactical motives behind the distribution of these grants. We find support for the hypothesis that the incumbent government used the grant program under study in order to win votes. In particular, we find strong support for the Lindbeck-Weibull/Dixit-Londregan model in which parties distribute transfers to regions where there are many swing voters. This result is statistically as well as economically significant. We do however not find any support for the model that predicts that the incumbent government transfer money to its own supporters.
urn:nbn:se:uu:diva-2469
Keywords: D72; H73; H77; 330; Political economy; Intergovernmental grants; Vote purchasing; Neue politische Ökonomie; Wahl; Ökonomische Theorie der Demokratie; Finanzausgleich; Schweden